Managing change for strategy implementation at the Aurum Institute - Kuwane, Bulelani (My University, 2015)
The research examines how The Aurum Institute (Aurum) managed change during the implementation of its 2010 strategy. The new strategy also included changes to the structure. Aurum is a not-for-profit, public benefit organisation. The purpose of the research was to investigate factors that led to resistance to change at Aurum. The research drew on Lewin’s Force- Field Theory of Change as a theoretical framework. This research adopted an interpretative social science approach. The design that the research took is a qualitative approach. Data was collected through semi-structured interviews conducted with ten people: eight current senior and middle managers at Aurum and two other interviewees, a former manager and a consultant. Data was analysed using the Successive Approximation Method. The results show that there was resistance to change at Aurum during strategy implementation and restructuring. The results also showed that there were good reasons for the organisation developing a strategy and organisational restructuring, and one of the main results was growing the organisation to ensure sustainability. The research showed that there was resistance to change as a result of multiple factors. These factors include, among other things, ownership of the change initiatives, that the implementation of the matrix structure was difficult, insufficient resources were allocated to change initiatives, and some people did not understand the need to change. It is recommended that the organisation builds leadership capacity and prioritises allocation resources to ensure that change initiatives are successful.
Keywords: Strategic planning -- South Africa. Organizational change -- South Africa.